Model' razdel'nogo upravleniya sportom dlya vsekh i sportom vysshikh rezul'tatov - Piloyan, R. A.; Suchanov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
Developmental peculiarities in sport managing are shown in the article. Several disputable points, determined by uncritical employ of physical culture theory and slight connection with the methodology of science, psychology and theory of sport are revealed. The gap between the theory and real practice of managing in physical education and sport in Russian Federation is the consequence of that. The model of distinctive managing by sport for all and elite sport offered by the authors could provide non-conflict developing of commonness and mastership in the country-scale.